1976
DOI: 10.1002/1097-0142(197609)38:3<1318::aid-cncr2820380334>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of a benign lymphoepithelial salivary gland lesion to lymphocytic lymphoma during dilantin therapy.Correlation with dilantin-induced lymphocyte transformation in vitro

Abstract: A patient with a classical salivary gland benign lymphoepithelial lesion (BLL) that converted to a lymphoblastic lymphoma (LSA) localized to the salivary glands is described. The malignant transformation of the BLL was preceded by Dilantin anticonvulsant therapy, and in vitro tests subsequent to the development of LSA demonstrated positive Dilantin-induced lymphocyte transformation. The lymphoma was treated successfully by local irradiation, chemotherapy, and discontinuation of Dilantin. The case illustrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…[28][29][30] While both Hodgkin's and non-Hodgkin's lymphomas have been associated with BLL, most have been non-Hodgkin's lymphomas. 28,29,31 Our series contained one patient in whom malignant lymphoma of a monocytoid B-cell type had apparently arisen in a gland affected by the BLL. This patient had massive bilateral enlargement of the parotids and, following FNA diagnosis of malignant lymphoma, bilateral biopsies of his parotid glands were performed.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] While both Hodgkin's and non-Hodgkin's lymphomas have been associated with BLL, most have been non-Hodgkin's lymphomas. 28,29,31 Our series contained one patient in whom malignant lymphoma of a monocytoid B-cell type had apparently arisen in a gland affected by the BLL. This patient had massive bilateral enlargement of the parotids and, following FNA diagnosis of malignant lymphoma, bilateral biopsies of his parotid glands were performed.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the malignant transformation in this group of diseases remains unknown but it should be pointed out that Lapes et al (1976) found that the administration of Dilantin, a drug frequently associated with other manifestations of drug hypersensitivity reaction (such as fever, eosinophilia and skin rash) induced a lymphocytic lymphoma is a woman with BLL.…”
Section: Discussionmentioning
confidence: 99%
“…The malignancies described are mainly reticuloendothelial. Pinkus and Dekker (1970), for example, described a 'reticulum cell sarcoma', Lapes et al (1976) wrote about a diffuse poorly differentiated lymphocytic lymphoma. Azzopardi and Evans (1971) described Hodgkin's disease as a complication of BLL and Sjogren's syndrome.…”
Section: Discussionmentioning
confidence: 99%